Determination of Teachers’ Food Allergy and Anaphylaxis Management Self-efficacy and Knowledge Levels - Aslan, GÃ¼lpÄ±nar; SAVCI BAKAN, AyÅŸe Berivan (Advances in Nursing & Midwifery, 2022)
Introduction:This study aims to determine teachers’ food allergy and anaphylaxis management self-efficacy and knowledge levels. Methods: This descriptive study was conducted with 399 teachers who worked in kindergarten and primary schools in a city center between March and June 2022. Data were collected through the Descriptive Characteristics Form and the Food Allergy and Anaphylaxis Management Self-efficacy Scale for School Personnel. Results: The average age of participating teachers was 31.18± 6.79 years, and 67.2% were females, 61.9% were married, 63.7% were classroom teachers, and 56.6% did not have children. Teachers’ Food Allergy and Anaphylaxis Management Self-Efficacy Scale mean score was 21.21±6.22. Self-efficacy was higher in kindergarten teachers, teachers who had a student with food allergy, those who received first aid education after starting to work, those who think that food allergy and anaphylaxis management in school is the teachers’ duty, and those who wanted to know about food allergy and anaphylaxis management. Teachers with low self-efficacy felt/would feel most frequently panic while managing a child with food allergy (p<0.05). Conclusions: This study found that food allergy and anaphylaxis management self-efficacy was affected by teachers’ area of specialization, presence of a student with food allergy, receiving first aid education, and thinking that teachers are responsible for the management of the process. Keywords: Food allergy, Anaphylaxis, Child, School Health, Teacher, Public health nursing